Neutropenia responsive to ketogenic diet in an infant with GLUT1 deficiency syndrome - Sørensen, Cristel M.; Ifversen, Marianne; Ek, Jakob; Uldall, Peter; Simonsen, Henrik (Journal of Pediatric Epilepsy, 2013)
Glucose transporter 1 deficiency syndrome (GLUT1-DS1) is a rare and complex congenital metabolic encephalopathy characterized by infantile seizures, movement disorder, delayed development and acquired microcephaly. GLUT1-DS1 is most often caused by a de novo heterozygous mutation of the gene encoding the GLUT1 transporter, SLC2A1. We present an otherwise classical case of GLUT1-DS1 presenting at 6 wk of age with seizures. The infant had unexplained neutropenia during the months preceding molecular diagnosis. Mutational analysis of the SLC2A1 gene identified a de novo novel heterozygous deletion of 26 nucleotides between exon 5 and 6. As expected, the treatment with ketogenic diet remedied the seizures, but surprisingly it also corrected the neutropenia. We cannot rule out that this might be a phenomenon of neutropenia as an unexplained association in this single patient, but this novel observation has led us to hypothesize that in a subset of susceptible individuals with GLUT1-DS1, disturbed myelopoieses may be an accompanying phenomenon, which may be explained by deficient energy flux in hematological progenitor cells.
Keywords: GLUT1-DS1; ketogenic diet; neutropenia